Remodeling of tumour microenvironment: strategies to overcome therapeutic resistance and innovate immunoengineering in triple-negative breast cancer - Singh, Desh Deepak; Haque, Shafiul; Kim, Youngsun; Han, Ihn; Yadav, Dharmendra Kumar (Frontiers in Immunology, 2024)
Triple-negative breast cancer (TNBC) stands as the most complex and daunting subtype of breast cancer affecting women globally. Regrettably, treatment options for TNBC remain limited due to its clinical complexity. However, immunotherapy has emerged as a promising avenue, showing success in developing effective therapies for advanced cases and improving patient outcomes. Improving TNBC treatments involves reducing side effects, minimizing systemic toxicity, and enhancing efficacy. Unlike traditional cancer immunotherapy, engineered nonmaterial’s can precisely target TNBC, facilitating immune cell access, improving antigen presentation, and triggering lasting immune responses. Nanocarriers with enhanced sensitivity and specificity, specific cellular absorption, and low toxicity are gaining attention. Nanotechnology-driven immunoengineering strategies focus on targeted delivery systems using multifunctional molecules for precise tracking, diagnosis, and therapy in TNBC. This study delves into TNBC’s tumour microenvironment (TME) remodeling, therapeutic resistance, and immunoengineering strategies using nanotechnology.